Analysis and Characterization of Factors Affecting the Consistency of Tl-201 Myocardial Perfusion Single-Photon Emission Computed Tomography and Coronary Angiography Results in Patients with Suspected Coronary Artery Disease - Fu-Ren Tsai; Hung-Pin Chan; Chun-Hao Yin; Jin-Shuen Chen; Yao-Shen Chen; Daniel Hueng-Yuan Shen (Diagnostics, 2025)
Background/Objectives: Tl-201 myocardial perfusion single-photon emission computed tomography (MPS) is a minimally invasive test for patients with suspected coronary artery disease (CAD). While its predictive and prognostic values are well established, diagnostic performance varies. A recent meta-analysis reported that the sensitivity and specificity of MPS range from 48.8 to 100% and 46.7 to 94.7%, respectively, reflecting discordance between CAG. Little is known, however, about the influence of patients’ characteristics and CAD risk factors on the diagnostic performance of MPS. This study aims to evaluate these factors in relation to MPS performance. Methods: We screened 4817 consecutive patients referred to our Nuclear Medicine Department in 2015 for Tl-201 MPS. Patients with clinically suspected ischemic heart disease who underwent CAG within 60 days post-MPS were included in the present analysis. The percentage of agreement/disagreement between the MPS-abnormal/normal and CAG-positive/negative groups was evaluated. Additionally, patient characteristics, CAD risk factors, co-morbidities, and single-photon emission computed tomography (SPECT) image-derived parameters were compared among the patients. Results: Among 635 patients with abnormal MPS, 583 had coronary stenosis. For the 52 without stenosis, causes included non-obstructive CAD (34.6%), prior infarction with scarring (32.7%), and imaging artifacts (32.7%). Significant stenosis was associated with older age, male sex, diabetes, dyslipidemia, CKD, and prior PCI, while hypertension and higher BMI were more common in insignificant CAD. Among 104 patients with normal MPS, 79 had stenosis, mainly in the LAD. Clinical risk factors were more prevalent in patients with any degree of stenosis. Conclusions: In patients with an abnormal MPS, the incorporation of visual interpretation, parameters, and CAD risk factors increases specificity and helps differentiate obstructive from non-obstructive CAD.